The effect of 26 versus 29-inch wheel diameter in the transmission of vibrations in cross-country mountain biking - Moreno Manas, E.; Llana-Belloch, S.; Úbeda-Pastor, V.; Garcia-Massó, X. (Sports Biomechanics, 2021)
Vibrations experienced by cyclists can affect their performance and health. We analysed the vibrations transmitted by mountain bike (26 or 29-inch wheels), in a 2,110 m circuit with a sample of 55 cyclists. The results indicate that the 29"-wheel increases speed (p <0.001) and thus performance but it also increases exposure to vibrations as the root mean square (RMS) indicate (p =0.001). The wheel diameter significantly affected the accelerometer-related dependent variables (p <0.01), specifically seen in the RMS variable (p <0.01). Regarding vibration transmission variables, it was found that the LW/FH, RW/FH, LA/RH, and RA/RH ratios were higher in the 29" bicycle than in 26" one. Average heart rate (p =0.01) and maximum heart rate (p <0.01) values were higher for the 29" bike with no significant differences in the average power values recorded. In conclusion, bicycles with 29" wheels transmit higher levels of vibration to riders.